1997
DOI: 10.1074/jbc.272.25.15765
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Expression of Ca2+ Channels in Pancreatic and Salivary Gland Cells

Abstract: In polarized epithelial cells [Ca 2؉ ] i waves are initiated in discrete regions and propagate through the cytosol. The structural basis for these compartmentalized and coordinated events are not well understood. In the present study we used a combination of [Ca 2؉ ] i imaging at high temporal resolution, recording of Ca 2؉ -activated Cl ؊ current, and immunolocalization by confocal microscopy to study the correlation between initiation and propagation of [Ca 2؉ ] i waves and localization of Ca 2؉ release ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
203
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(222 citation statements)
references
References 33 publications
15
203
4
Order By: Relevance
“…The results with the mAb were not conclusive, because of low signal/noise with this mAb in SMG cells (not shown). The pattern of expression of SERCA2b in SMG cells resembled the labeling obtained with all Ca 2ϩ release channels (7).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…The results with the mAb were not conclusive, because of low signal/noise with this mAb in SMG cells (not shown). The pattern of expression of SERCA2b in SMG cells resembled the labeling obtained with all Ca 2ϩ release channels (7).…”
Section: Resultssupporting
confidence: 60%
“…The most problematic aspect of the mechanism described above is that we could not find Ca 2ϩ release channels in any part of the cells, except underneath the luminal and lateral membranes and in the nuclear envelope (7). This raises the question of how [Ca 2ϩ ] i increases uniformly in all parts of the cells without redistribution of Ca 2ϩ release channels.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The primary sequences also show differences in consensus phosphorylation and Nglycosylation sites [9]. In addition, it has been suggested that individual isoforms may be localized to discrete regions of the cell [10][11][12] or that specific isoforms may regulate distinct cellular processes such as Ca# + entry across the plasma membrane [10] or apoptosis [11,13]. Overall, the presence of differentially regulated IP $ R isoforms with the ability to form hetero-oligomers provides the cell with considerable flexibility in the regulation of Ca# + signals.…”
Section: Introductionmentioning
confidence: 99%